Formy „wychowywania i umoralniania” chłopów propagowane na łamach pism pozytywistów warszawskich (do 1886 r.) - Kita, Jarosław (Acta Universitatis Lodziensis. Folia Historica, 1995)
The positivists declared the programme of the emancipation of lower classes of the society. That programme was aimed at the final removal of class deserimination and at allowing people the equal social and civil rights. It was associated with demands for wide changes tu the countryside of the Polish Kingdom. The most important of the postulates were those of development of the culture of the education and of the morals of the peasants. In this article the ways and the forms of realization of postulations are so presented. They were propagated by the positivists in their publications.